1988
DOI: 10.1021/ie00075a020
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of hydrogen sulfide, sulfur dioxide, carbon dioxide, propane, and n-butane in poly(glycol ethers)

Abstract: Sulfur Removal Process. An automated gas solubility measurement system was used to collect data on the solubility of hydrogen sulfide, carbon dioxide, propane, and n-butane in a variety of these solvents. The partial pressure of solute gas in these experiments was between 3 and 100 kPa. Correlations for Henry's law coefficients are given as a function of temperature. Gas solubility in the organic solvents decreases when small amounts of water (<6 wt %) are also present. Gas solubility in solvent-water mixtures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
48
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 2 publications
7
48
2
Order By: Relevance
“…He used the Peng Robinson equation of state to calculate the fugacities of CO 2 , and the Krichevsky-Illinskaya equation to extract Henry's Law constants. Values of Henry's Law constants at 25 °C were on average 18 % higher than those measured by Sciamanna et al (1988) for DEGDME, TEGDME, TTEGDME and TTEGMBE. Sciamanna used an automated procedure to make the solubility measurements.…”
Section: Resultscontrasting
confidence: 53%
See 1 more Smart Citation
“…He used the Peng Robinson equation of state to calculate the fugacities of CO 2 , and the Krichevsky-Illinskaya equation to extract Henry's Law constants. Values of Henry's Law constants at 25 °C were on average 18 % higher than those measured by Sciamanna et al (1988) for DEGDME, TEGDME, TTEGDME and TTEGMBE. Sciamanna used an automated procedure to make the solubility measurements.…”
Section: Resultscontrasting
confidence: 53%
“…In the case of a mixture of solvents, a high selectivity of physical solvents to the acid gases over the hydrocarbon is best achieved by control of solvent polyglyme distribution, water content, and operating conditions. Sciamanna and Lynn (1988) measured the solubility of CO 2 , H 2 S, propane and n-butane in fi ve glycol ethers (DEGDME, TEGDME, TTEGDME, DEGMME, TEGMBE) with an automated gas solubility measurement and reported the results in the form of Henry's law constants at infi nite dilution at 25 °C. Sweeney et al (1988) reported the solubility of CO 2 in DEGDME, TEGDME, and TTEGDME at 25 °C.…”
Section: Randd Notementioning
confidence: 99%
“…For polyethylene glycol ethers (glymes) such as diethylene glycol dimethyl ether (diglyme), triethylene glycol dimethyl ether (triglyme), and tetraethylene glycol dimethyl ether (tetraglyme), Sciamanna and Lynn [2] had previously reported about the carbon dioxide solubility between 3 and 100 kPa. Henni et al [3] had also measured Henry's law constant at 25, 40, and 60 • C by gas chromatographic analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The calculated results for Selexol are compared with the other glymes investigated by Sciamanna and Lynn (1988) and Dernyanovich and Lynn (1987) in the sulphur dioxide-glyme mixture is weaker than the sulphur dioxide-amine bond resulting in lower energy requirements for solvent regeneration.…”
Section: Heat Effecq Accompanying S 0 2 Absorptionmentioning
confidence: 99%
“…It was shown that the structure of the hydrocarbon skeleton had a negligible effect of the solvent power. (Sciamanna and Lynn, 1988).…”
mentioning
confidence: 99%